Citizens' blame of politicians for public service failure: experimental evidence about blame reduction through delegation and contracting - James, Oliver et al (2016)
Theories of blame suggest that contracting out public service delivery reduces citizens' blame of politicians for service failure. The authors use an online experiment with 1,000 citizen participants to estimate the effects of information cues summarizing service delivery arrangements on citizens' blame of English local government politicians for poor street maintenance. Participants were randomized to one of four cues: no information about service delivery arrangements, politicians' involvement in managing delivery, delegation to a unit inside government managing delivery, and delegation through a contract with a private firm managing delivery. The politicians managing delivery cue raises blame compared to citizens having no information. However, the contract with a private firm cue does not reduce blame compared to either no information or the politicians managing delivery cue. Instead, the delegation to a unit inside government cue reduces blame compared to politicians managing delivery, suggesting that delegation to public managers, not contracting, reduces blame in this context. - Reproduced.
Keywords: Public utilities